2021
DOI: 10.1115/1.4049305
|View full text |Cite
|
Sign up to set email alerts
|

Shape Optimization of Thermoacoustic Systems Using a Two-Dimensional Adjoint Helmholtz Solver

Abstract: Thermoacoustic instabilities, which arise due to the interaction between flames and acoustics, are sensitive to small changes to the system parameters. In this paper, we apply adjoint-based shape optimization to a 2D finite element Helmholtz solver to find accurately and inexpensively the shape changes that most stabilise a 2D thermoacoustic system in the linear regime. We examine two cases: a Rijke tube and a turbulent swirl combustor. Both systems exhibit an unstable longitudinal mode and we suppress the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…to design variables can therefore be computed cheaply using adjoint methods; this information is then utilized by an optimization routine from the gradient descent family to arrive at a stabilized design. Adjoint-based sensitivity analysis has been applied to low-order network models by Magri and Juniper 2 , Mensah and Moeck 3 , Silva et al 4 , to 2D Helmholtz equation models by Falco and Juniper 5 and to 3D Helmholtz models by Mensah et al 6 . A comprehensive review of the use of adjoints in thermoacoustics can be found in Magri 7 .…”
Section: Introductionmentioning
confidence: 99%
“…to design variables can therefore be computed cheaply using adjoint methods; this information is then utilized by an optimization routine from the gradient descent family to arrive at a stabilized design. Adjoint-based sensitivity analysis has been applied to low-order network models by Magri and Juniper 2 , Mensah and Moeck 3 , Silva et al 4 , to 2D Helmholtz equation models by Falco and Juniper 5 and to 3D Helmholtz models by Mensah et al 6 . A comprehensive review of the use of adjoints in thermoacoustics can be found in Magri 7 .…”
Section: Introductionmentioning
confidence: 99%